From Zero to a National Data Set in 2 Weeks: Reflections on a COVID-19 Collaborative Survey Project. (August 2020) - Hargittai, Eszter; Nguyen, Minh Hao; Fuchs, Jaelle; Gruber, Jonathan; Marler, Will; Hunsaker, Amanda; Karaoglu, Gökçe
In March 2020, like much of the rest of the world, we went into lockdown. A week into our new reality, we decided to do a survey study about how people were experiencing the COVID-19 pandemic. In this piece, we describe what motivated us to do the study, how we went about it, and what others can learn from our experiences.